Efficacy and Safety of Adherence to dl-3-n-Butylphthalide Treatment in Patients With Non-disabling Minor Stroke and TIA—Analysis From a Nationwide, Multicenter Registry - Tan, Zefeng; Zhao, Yin; Yang, Wanyong; He, Shenwen; Ding, Yan; Xu, Anding (Frontiers in Neurology, 2021)
Background Dl-3-n-Butylphthalide (NBP) has shown the efficacy of improving clinical outcomes in acute ischemic stroke by enhancing collateral circulation. We aimed to evaluate the efficacy and safety of NBP in patients with non-disabling minor ischemic stroke. Methods The BRIDGE (the observation study on clinical effectiveness of NBP on patients with non-disabling ischemic cerebrovascular disease) is a prospective registry to monitor the efficacy and safety of NBP therapy in acute non-disabling ischemic stroke or high-risk TIA. Non-disabling minor ischemic stroke patients within 48 hours were enrolled across 51 stroke centres in China. We divided patients into NBP compliance or non-compliance groups according to their adherence with NBP. The primary outcome was the favourable functional outcome at 90days, defined as a modified Rankin scale(mRS) <2 Results Between 10th October 2016 and 25th June 2019, 3118 patients were included in this analysis. In multivariable analysis, after adjusted for common risk factors and demographic factors, NBP-compliance group has a higher proportion of favourable functional outcome (92.1%vs. 87.4%, adjusted odds ratio1.86, 95% confidence interval, 1.41-2.45), and a higher stroke recurrence rate (2.40% vs 0.31%, adjusted odds ratio 7.85, 95% confidence interval, 3.22-19.18) than the NBP-non-compliance group. There was no significant difference in death and intracranial haemorrhage rate between the two groups. In subgroup analysis, patients with NIHSS scores from 3 to 5 who complied to NBP therapy had a higher rate of favourable functional outcomes than the NBP-non-compliance group. (89.8% vs 76.8%, adjusted odds ratio 2.54 (1.64-3.93), adjusted interaction P= 0.001) Conclusion In non-disabling minor ischemic stroke or TIA, compliance with NBP therapy resulted in more favourable functional outcomes, and this effect may be more pronounced in patients with NIHSS scores of 3-5. Further large randomised, double-blind controlled studies to analyse the association between NBP and functional outcome is warranted in the coming future.